Anticipating, experiencing and overcoming challenges in clinical academic training. Issue 8 (2nd August 2021) - Trusson, Diane; Rowley, Emma; Barratt, Jonathan
Abstract : Background/Aims: This article builds on studies that have reported on the challenges of pursuing a clinical academic career. It aims to explore the perceived challenges that clinical academic trainees experience, and the ways in which they overcome them. Methods: Data were collected from clinical academic trainees via an online survey and semi-structured interviews, then thematic analysis was performed. Results: The trainees experienced challenges relating to balancing and progressing a clinical academic career. They sought to overcome these through self-efficacy and by drawing on the support of peers, supervisors and mentors. Conclusions: Clinical academic trainees experience significant challenges as they strive to develop careers in academic medicine. They draw on their own resources and the support of others to help them to overcome these challenges. They also often act to advocate, advise and support other aspiring clinical academics.